2014
DOI: 10.2166/wp.2014.092
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of farmers' willingness to participate in water trading in southern Spain

Abstract: This study applies contingent valuation to assess farmers' willingness to trade irrigation water. We analyse farmers' willingness to pay for water and their willingness to accept the selling of water through a seasonal market, under both normal rainfall and drought conditions. A survey of 241 farmers (irrigators and non-irrigators) in the Guadalquivir River Basin and in the Mediterranean (Almanzora) Basin in southern Spain is used as a basis to construct the irrigation water supply and demand curves for both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Benefits derived from voluntary water reallocation often do not meet expectations because participation is relatively limited—water transfers in many markets are around 2–5% of total water demand . Giannoccaro et al, along with Tisdell and Ward, argue that the overestimation of benefits by theoretical water market models is because stakeholder's perceptions and values are not considered. Many water users, especially farmers (which hold the majority of water entitlements), exhibit a general aversion to the commoditization of water through market mechanisms, instead preferring that a public entity maintain control of water allocations .…”
Section: Impediments To Effective Water Reallocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits derived from voluntary water reallocation often do not meet expectations because participation is relatively limited—water transfers in many markets are around 2–5% of total water demand . Giannoccaro et al, along with Tisdell and Ward, argue that the overestimation of benefits by theoretical water market models is because stakeholder's perceptions and values are not considered. Many water users, especially farmers (which hold the majority of water entitlements), exhibit a general aversion to the commoditization of water through market mechanisms, instead preferring that a public entity maintain control of water allocations .…”
Section: Impediments To Effective Water Reallocationmentioning
confidence: 99%
“…Many water users, especially farmers (which hold the majority of water entitlements), exhibit a general aversion to the commoditization of water through market mechanisms, instead preferring that a public entity maintain control of water allocations . The distrust of water markets have been shown to stem from beliefs that markets will disadvantage low‐income farmers, perceptions water and land rights should not be separated, and views that water should not be treated as a commercial good . However, Bjornlund and Giannoccaro et al have shown that these negative perceptions of water transfers are somewhat abated over time and drought induced water scarcity acts as a catalyst to market involvement .…”
Section: Impediments To Effective Water Reallocationmentioning
confidence: 99%
“…Water accounts for a low share of total costs, but farmers are acutely aware of the politically negotiable price they pay. According to Giannoccaro, Castillo, and Berbel (2015), a representative sample of farmers from Almería are willing to pay $0.44/ m 3 under normal conditions, and $0.63/m 3 under drought conditions. Those values explain their lack of interest in desalinated supplies that cost more than other sources.…”
Section: Groundwater or Exports In Almería?mentioning
confidence: 99%
“…Giannoccaro et al, and Ortiz and Ceña [42,59,60] show farmers' resistance to trading water in Spain due to both their view of water as a non-tradable common good and the notion that water rights should not be separated from land. Cultural barriers have been largely recognized in other countries [31,56], suggesting that farmers' perceptions and preferences play an essential role in discouraging their participation in water markets.…”
Section: Farmers' Perceptions and Preferencesmentioning
confidence: 99%
“…However, and despite the narrowness of water markets, differences in water productivity between buyers and sellers allowed water markets to achieve their targets as an instrument for water reallocation when needed [60].…”
Section: Proposals To Improve Water Markets In Spainmentioning
confidence: 99%